Analysis of Performance and Energy Efficiency for Multi-User Mimo 6G Network Using Beamforming Methods - Muhammad Farhan Haikal; Yunida Yunida; Nasaruddin Nasaruddin (Journal of Applied Engineering and Technological Science)
This paper addresses the challenge of high energy consumption in sixth-generation (6G) multi-user multiple-input multiple-output (MU-MIMO) networks by analyzing how different beamforming techniques impact network performance and energy efficiency. Simulations were performed in a sub-THz communication environment using analog, digital, and hybrid beamforming across various base station antenna configurations (64, 128, and 256 elements) and user densities to evaluate performance metrics (such as received power and signal-to-interference-plus-noise ratio) alongside energy consumption. The results show that larger antenna arrays (e.g., 256 elements) provide significantly higher signal quality and received power but require more energy. In contrast, smaller arrays (e.g., 64 elements) use less power at the cost of performance. Digital beamforming with a moderate array size (128 antennas) yields the highest energy efficiency, while hybrid beamforming with the largest array results in the lowest energy efficiency. These findings imply that carefully selecting the beamforming method and antenna array size can balance performance with energy efficiency, guiding the design of more sustainable 6G networks. The novel contribution of this research is a comprehensive comparative analysis of analog, digital, and hybrid beamforming in a 6G MU-MIMO context, providing new insights for optimizing future 6G network deployments.